(untitled) (Journal of Hama University, 2025)
This research aims to explore the obstacles which prevent undergraduate female students from practicing sport, and studying the differences in levels of obstacles according to the variables social situation and economical position. It has been used the descriptive approach using a questionnaire designed by the two researchers, which has been applied at a sample of (400) females students non practiced the sport activity from different faculties in Damascus university. The results showed that the academic and economical obstacles prevent undergraduate female students from practicing sport more than the social, religious and psychological obstacle. As results showed high levels of religious, psychological and social obstacles which prevent from practicing sport among married and engaged female students more than among the single female students. In light of study’s results, it was recommended to addressing the obstacles of practicing sport in a way that suits the nature of each type of these obstacles, and activating the role of student union in spreading awareness campaigns on the importance of adopting healthy sports practices by female students.